Hubungan Kekuatan Otot Lengan Terhadap Kemampuan Passing Bawah pada Permainan Bolavoli (Studi Pada Klub Bolavoli Bong Volleyball Club Kota Pasuruan) - Firman Kurnia Hajar Dewantara; Garnika Ade Sinto Raya (Jurnal Multidisiplin Madani, 2022)
Passing is the most basic technique in a volleyball game and usually the down pass is also called the forearm pass. The aims of this study were to determine: (1) whether there was a significant relationship between arm muscles and the ability to pass down the athletes of the Pasuruan bong volleyball club; (2) the presence or absence of the level of arm muscle strength with the ability to pass down in the athletes of the bong volleyball club of the Pasuruan city club. The target of this study was the male athletes of the Bong Volleyball Club, Pasuruan City, totaling 16 athletes. The type of research used in this research is correlational research. The data collection process was carried out by testing the strength of the arm muscles using a push up test for 30 seconds and a passing down test using the Brady Wall Volly Test. Furthermore, the research data were analyzed using the SPSS 22.0 series. The results showed: (1) There was a significant relationship between arm muscle strength and lower passing ability with a significance value of 0.010 < 0.05.